Biomarkers of Activation and Inflammation to Track Disparity in Chronological and Physiological Age of People Living With HIV on Combination Antiretroviral Therapy - Thurman, Michellie; Johnson, Samuel; Acharya, Arpan; Pallikkuth, Suresh; Mahesh, Mohan; Byrareddy, Siddappa N. (Frontiers in Immunology, 2020)
With advancement, prompt use, and increasing accessibility of antiretroviral therapy, people with HIV are living longer and have comparable lifespans to seronegative people. However, people living with HIV experience tradeoffs with quality of life often developing age-associated conditions such as cancers, cardiovascular diseases, or neurodegeneration due to chronic immune activation and inflammation. This creates a discrepancy in chronological and physiological age, with HIV-infected individuals appearing older than they are, and in some contexts ART-associated toxicity exacerbates this gap. The complexity of the accelerated aging process in the context of HIV-infection highlights the need for greater understanding of biomarkers involved. In this review, we discuss markers isolated from different anatomical sites of the body including periphery, brain, and gut, as well as markers related to DNA that may serve as reliable predictors of accelerated aging in HIV as it relates to inflammatory state and immune activation.